2018
DOI: 10.5152/iao.2018.5500
|View full text |Cite
|
Sign up to set email alerts
|

Audiovestibular Loss of Function Correlates in Vestibular Schwannomas

Abstract: OBJECTIVES:The aim of the present study was to investigate the relationships between tumor size, hearing, and vestibular outcomes in patients with vestibular schwannomas (VSs). MATERIALS and METHODS:Adult patients (n=124) with unilateral extrameatal VS prior to surgery were included in the study. This was a retrospective cohort study of preoperative audiovestibular investigations including audiometry, discrimination test, caloric test, cervical vestibular evoked myogenic potential (c-VEMP), and ocular vestibul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
(46 reference statements)
0
11
0
Order By: Relevance
“…Intuitively, the larger tumor may lead to severer compression, which will affect their blood supply and lead to neurosensory hearing deficits by subsequent ischemic changes. However, in this systematic review, the majority of the retrieved studies (8/14, 57.1%) suggest the degree of hearing loss do not correlate with tumor size/volume (16)(17)(18)(19)(20)(21)(22)(23). At the beginning of this millennium, Sakamoto et al found no correlation between hearing loss speed and tumor size at the initial diagnosis (16).…”
Section: Tumor Size/volumementioning
confidence: 75%
See 3 more Smart Citations
“…Intuitively, the larger tumor may lead to severer compression, which will affect their blood supply and lead to neurosensory hearing deficits by subsequent ischemic changes. However, in this systematic review, the majority of the retrieved studies (8/14, 57.1%) suggest the degree of hearing loss do not correlate with tumor size/volume (16)(17)(18)(19)(20)(21)(22)(23). At the beginning of this millennium, Sakamoto et al found no correlation between hearing loss speed and tumor size at the initial diagnosis (16).…”
Section: Tumor Size/volumementioning
confidence: 75%
“…and West et al. further grouped SVS according to the extrameatal diameter (from small SVS <1 cm to giant tumor >4 cm) and found no significant correlation between hearing function and tumor grade ( 21 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The aforementioned test batteries should be performed at the onset of the audiovestibular symptoms and during followup to monitor the course of the disease. The analysis of the relationships between tumour size, hearing, and vestibular outcomes in 124 patients with unilateral extrameatal vestibular schwannoma undergoing preoperative audiovestibular investigations such as audiometry, discrimination test, caloric test, cervical vestibular evoked myogenic potential and ocular vestibular evoked myogenic potential reveals significant a difference between lesioned and non-lesioned ear for all audiovestibular outcomes (6). Cervical vestibular evoked myogenic potential deficit is significantly associated with severe hearing loss and larger tumours.…”
Section: Audiovestibular Medicine -A New Paradigmmentioning
confidence: 98%